2018
DOI: 10.1089/fpd.2018.2445
|View full text |Cite
|
Sign up to set email alerts
|

Loop-Mediated Isothermal Amplification forSalmonellaDetection in Food and Feed: Current Applications and Future Directions

Abstract: Loop-mediated isothermal amplification (LAMP) has become a powerful alternative to polymerase chain reaction (PCR) for pathogen detection in clinical specimens and food matrices. Nontyphoidal Salmonella is a zoonotic pathogen of significant food and feed safety concern worldwide. The first study employing LAMP for the rapid detection of Salmonella was reported in 2005, 5 years after the invention of the LAMP technology in Japan. This review provides an overview of international efforts in the past decade on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
61
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(64 citation statements)
references
References 122 publications
1
61
0
Order By: Relevance
“…Results indicate that this method is as specific as standard PCR methods and is extremely sensitive. The detection limit is 7.3 × 10 1 CFU/mL, which is more sensitive than that in many previous reports ( Yang et al., 2018 ) and is 1,000-fold greater than that in the national standard PCR method. The comparison between results of the clinical test used the visualized LAMP method, and those using the national standard PCR method showed that both methods caused missed detections.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…Results indicate that this method is as specific as standard PCR methods and is extremely sensitive. The detection limit is 7.3 × 10 1 CFU/mL, which is more sensitive than that in many previous reports ( Yang et al., 2018 ) and is 1,000-fold greater than that in the national standard PCR method. The comparison between results of the clinical test used the visualized LAMP method, and those using the national standard PCR method showed that both methods caused missed detections.…”
Section: Discussionmentioning
confidence: 60%
“…Existing methods of LAMP observation mainly include turbidity analysis, gel electrophoresis, the addition of fluorescent dyes, and colorimetry. Furthermore, some methods also require special expensive monitoring equipment or the opening of tube lids after the reaction ( Yang et al., 2018 ). This can easily cause aerosol contamination and is not suitable for clinical use.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, the LAMP assay has been widely used in food safety, pathogen and microbiological testing, clinical diagnosis, and so on. [6][7][8][9] LAMP assays are also an effective tool for screening genetic mutations. 10 A previous study detected the -SEA (Southeast Asian) deletion, and IVSII-I G>A mutation indicating thalassemia using LAMP assays.…”
Section: Introductionmentioning
confidence: 99%
“…Various commercial products combining isothermal DNA amplification assays with portable platforms have become available in recent years. While most of them detect causative agents in clinical specimens, some platforms also employ ready-to-use test kits for applications in food and environmental analysis [ 24 ]. This includes the Loopamp Realtime Turbidimeter, an instrument for measuring the turbidity generated by the LAMP reaction in real time in combination with reagent kits to detect pathogens in foods and water (e.g., Salmonella , Listeria , Legionella , and Cryptosporidium ).…”
Section: Commercialized Isothermal Methods For Food and Water Analysimentioning
confidence: 99%
“…Among the four steps covered in this section, this is where most of the work has been done in recent years. Moreover, many isothermal DNA amplification methods targeting important pathogens have already been diligently studied or evaluated, such as LAMP assays to detect Salmonella in food and feed by the Food and Drug Administration of the United States [ 24 ]. Although the abovementioned MIQE guidelines have been defined primarily for qPCR experiments, it will be of utmost importance to extend them to isothermal DNA amplification assays to establish certain quality standards in the future.…”
Section: Case Study: Towards Implementing a Field-applicable Workflowmentioning
confidence: 99%